Characterization of phytochemicals in Costa Rican guava (Psidium friedrichsthalianum -Nied.) fruit and stability of main compounds during juice processing - (U)HPLC-DAD-ESI-TQD-MSn - Rojas Garbanzo, Carolina (2019)
Psidium fruits are well known in tropical countries as a food and have traditionally been used for the treatment of some diseases, e.g., diarrhea and diabetes. Among them, P. friedrichsthalianum has been associated with positive health effects caused by polyphenols and vitamin C, but detailed information on the phytochemicals involved and their stability during processing is scarce. This study addresses the characterization and quantification of phytochemicals in the peel and flesh of P. friedrichsthalianum using UHPLC-DAD-ESI-MS/MS. Over 100 compounds were characterized, among them proanthocyanidins, ellagitannins, flavanolignans, biflavonoids, and dihydrochalcones. The content of polar secondary metabolites in the peel was approximately 30% higher than in the flesh. B-type proanthocyanidins represented 52.2% and 35.8% in peel and flesh, respectively. During juice processing, geraniin and vescalagin were not affected, whereas other compounds underwent some changes. Castalagin isomers were negatively affected, but pedunculagin isomers, cinnamoyl-O-hexoside, and citric, succinic, and dehydroascorbic acids contents increased. This report highlights the importance of considering Costa Rican guava as a good source of condensed and hydrolysable tannins, i.e., proanthocyanidins and ellagitannins, respectively. Besides, this fruit seems to be a potential raw material for the development of foods, e.g., juice, containing phytochemicals that showed to be stable during pasteurization.